Conceptualizing Social Outcomes of Large Marine Protected Areas. Issue 6 (2nd November 2017) - Gruby, Rebecca L.; Fairbanks, Luke; Acton, Leslie; Artis, Evan; Campbell, Lisa M.; Gray, Noella J.; Mitchell, Lillian; Zigler, Sarah Bess Jones; Wilson, Katie
ABSTRACT: There has been an assumption that because many large marine protected areas (LMPAs) are designated in areas with relatively few direct uses, they therefore have few stakeholders and negligible social outcomes. This article challenges this assumption with diverse examples of social outcomes that are distinctive in LMPAs. We define social outcomes as inclusive of both social change processes and social impacts, where "social" includes all perceptual or material human dimensions. We draw on five in-depth case studies to report social outcomes resulting from proposed or designated LMPAs in Bermuda, Rapa Nui (Easter Island), Kiribati, Palau, and the Commonwealth of the Northern Mariana Islands & Guam. We conclude: (1) social outcomes arise even in remote LMPAs; (2) LMPA efforts generate social outcomes at all stages of development; (3) LMPAs have the potential to produce outcomes at a higher level of social organization, which can change the scope and type of affected populations and, in some cases, the nature and stakes of the outcomes themselves; (4) the potential for LMPAs to impart distinctive social outcomes results from their unique geographies and/or intersection with high-level politics and policy processes; and (5) social outcomes of LMPAs may emerge in the form of social change processes and/or social impacts.